Fatores de risco e proteção aos adolescentes quanto ao uso de álcool e drogas: os desafios para as políticas públicas - (:unkn) unknown (Universidade Federal do Pampa, 2025)
The focus of this final project is to identify risk and protective factors for adolescents in relation to alcohol use, which involves other social contexts such as family, environment, school, peers, media and community. The theoretical framework was based on bibliographic research that concluded that to address the problem presented, it would be necessary to promote healthy growth and development, greater social equality and opportunities for adolescents and their families, acting against poverty and prejudice, implementing protective factors, public policies and compliance with the ECA to reduce behavioral and risk problems. Preventing alcohol consumption should be synonymous with healthy living. It is not enough to focus on the risks, but on the adolescent as a whole, using approaches that value quality of life.
Keywords: Adolescentes; Álcool; Drogas; Adolescentes - Uso de drogas; Brasil. [Estatuto da criança e do adolescente (1990)]; Adolescentes – Proteção; Política Pública; Adolescentes - Fatores de risco; Adolescents; Alcohol; Drugs; CNPQ::CIENCIAS HUMANAS